Porous Ge@C materials via twin polymerization of germanium(ii) salicyl alcoholates for Li-ion batteries. Issue 7 (1st February 2016) - Kitschke, Philipp; Walter, Marc; Rüffer, Tobias; Seifert, Andreas; Speck, Florian; Seyller, Thomas; Spange, Stefan; Lang, Heinrich; Auer, Alexander A.; Kovalenko, Maksym V.; Mehring, Michael
Abstract : Porous Ge@C materials as anode materials for Li-ion batteries were synthesized by the novel concept of twin polymerization starting from germylenes based on salicyl alcoholates. Abstract : The germylenes, germanium(ii ) 2-(oxidomethyl)phenolate (1 ), germanium(ii ) 4-methyl-2-(oxidomethyl)phenolate (2 ) and germanium(ii ) 4-bromo-2-(oxidomethyl)phenolate (3 ) were synthesized and their thermally induced twin polymerization to give organic–inorganic hybrid materials was studied. The compounds1–3 form oligomers including dimers, trimers and tetramers as a result of intermolecular coordination of the benzylic oxygen atom to germanium. The structural motifs were studied by single crystal X-ray diffraction analysis and DFT-D calculations. Thermally induced twin polymerization of these germylenes gave hybrid materials based on germanium-containing phenolic resins. Carbonization of these resins under reductive conditions resulted in porous materials that are composed of germanium and carbon (Ge@C materials), while oxidation with air provided non-porous germanium dioxide. The porous Ge@C materials were tested as potential anode materials for rechargeable Li-ion batteries. Reversible capacities of 540 mA h g −1 were obtained at a current density of 346 mA g −1 without apparent fading for 100 cycles, which demonstrates that germanium is well accessible in the hybrid material.